Perbandingan kuantitatif bahasa Miri dengan bahasa Melayu (Jurnal Bahasa, 2001)
Miri language is a type of Austronesian language which is spoken by a group of speakers known as Miri. It is grouped under Lower Baram languages, a subgroup of Sarawakan languages, which also comprises languages such as Dalik, Berawan, Kiput, Narum, Lelak and Lementing, Belait and Tutong. This article will offer a linguistic comparative discussion of this language by observing and identifying the basic vocabulary of the language, and comparing the basic vocabulary of the language with Malay language. The observation and identification of basic vocabulary will employ the 100 and 200 word lists by Morris Swadesh. The comparison between the two languages will determine the genetic relationship between Miri and Malay. This article represents a small contribution towards the process of documentation of the linguistic aspect of Miri language in view of its verge of extinction due to the fact that its speakers (especially the younger generation) have shifted to the Sarawak Malay for sociolinguistic reasons (Bibi Aminah Abdul Ghani dan Abang Ahmad Ridzuan 1993).